Integration of Artificial Intelligence In Management Talent For Improving Company Performance: Mediation Employee Engagement - Arif Syaifudin; Teguh Pradana; Muhammad Fatkhur Rozi (Yayasan Riset dan Pengembangan Intelektual, 2024)
Revolution Industry be one of part most important in activities in the company . The number of tasks that are routine done a individual so that matter the can give impact inability a individual do task the because of reach limit maximum physique a human. Intelligence artificial intelligence (AI) provides A offer related with potential transformational For improvement as well as give offer For replace task man in field intellectual , social and also industry In researcher data collection involving 94 leaders company food and beverages in the district area Pasuruan with using primary data. Maintaining talented employees , Support? Culture Organization , Reducing Workload? Employee own influence direct and significant to Company performance , good in a way direct and also through Engagement mediator Employees . Next Engagement Mediator Employee play a role as connector between variable independent and dependent , which indicates that There is influence partial .